Diversity of respiratory viruses present in nasal swabs under influenza suspicion in respiratory disease cases of weaned pigs - Martín-Valls, Gerard E.; Li, Yanli; Díaz, Ivan; Cano, Esmeralda; Sosa-Portugal, Silvana; Mateu, Enric (Frontiers in Veterinary Science, 2022)
Respiratory disease in weaned pigs is a common problem with a complex aetiology involving both viruses and bacteria. In the present study, we investigated the presence of eleven viruses in nasal swabs collected from nurseries (55 cases) under suspicion of swine influenza A virus (swIAV) and submitted by veterinarians for diagnosis. The other ten viruses included in the study were influenza B (IBV) and influenza D viruses (IDV), Porcine reproductive and respiratory syndrome virus (PRRSV), Porcine respiratory coronavirus (PRCV), Porcine cytomegalovirus (PCMV), porcine circoviruses 2 (PCV2), 3 (PCV3) and 4 (PCV), Porcine parainfluenza 1 virus (PPIV1) and Swine orthopneumovirus (SOV). Twenty-six swIAV-positive cases and twenty-nine cases of swIAV-negative respiratory disease were primarily established. IBV, IBV, PCV4 and PPIV1 were not found in any of the cases, while PRCV, SOV, and PCMV were more likely to be found in swIAV-positive nurseries with respiratory disease (p<0.05). Overall, PCV3, PRRSV, and PCMV were the most frequently detected agents on herd level. At an individual level, the prevalence of different viruses was: swIAV 48.6%; PRCV 48.0%; PRRSV 31.6%; SOV 33.8%; PCMV 48.3%, PCV2 36.0%; and PCV3 33.0%. Moreover, low Ct values (< 30) were common for all agents except for PCV2 and PCV3. When the correlation between different pathogens was examined at an individual level, it was found that presence of PRRSV was negatively correlated with swIAV and PRCV and was positively associated to PCMV (p<0.05). PRCV and SOV were positively correlated between them and negatively correlated with PCMV. Besides, analysis of samples of suckling pigs collected in subclinically infected farrowing units under an influenza monitoring program showed that circulation of PRCV, PCMV, SOV, and PCV3 started in the early weeks of life. Interestingly, in those subclinically infected units none of the pathogens was found to be correlated to the other. Overall, our data may contribute to a better understanding of the complex aetiology and the epidemiology of respiratory disease in weaners. This is the first report of SOV in Spain and shows for the first time the dynamics of this pathogen in swine farms.